Intelligent Robotic System for Fire Fighting - Srivastava, Surabhi; Yadav, Ritesh; Chauhan, Usha (International Journal of Data Science, 2021)
Fire-fighters faces several risks on jobs like burns, heat exhaustion and also they come in contact with high levels of carbon monoxide and other toxic hazards that put them at greater risks. This system is designed with the help of raspberry pi module which is integrated with ultrasonic sensor to avoid obstacles and pi camera which helps to detect fire or smoke using YOLOV2 Convolution neural network and also live video streaming is done that can be accessed by nearest fire fighting station through a web page. An aluminium sheet is used to make the body of the robotic system to protect it from high temperatures which can resist heat up to 700 centigrade. This intelligent robotic system performs many tasks and reduces damages caused by fire and also helps in saving lives of human fire-fighters.